Dietary Restrictions: Life at College. Issue 2 (1st June 2020) - Shaker, Dana; Matteson, Emily
Abstract: This ethnographic study seeks to understand the quality of life for residential undergraduate college students in the United States who restrict their diets either by choice or medical necessity. Since all kinds of dietary restrictions present similar lifestyle challenges not experienced by non‐dietary‐restricted residential college students, we define dietary restrictions broadly. A review of the existing research literature on dietary restrictions reveals that most studies are biomedical, focusing on clinical, cognitive, and psychological aspects of dietary restrictions. Few studies explore college students exclusively as a population, and even fewer consider how the social and material conditions of a college environment affect the lived experiences of dietary‐restricted students. This ethnography remedies the absence of qualitative and ethnographic research with a study of twenty‐nine individuals, most of whom are students who restrict their diets, across five undergraduate private college campuses over a fifteen‐week period in the spring of 2012. Our results add a new dimension to the biomedical research, which has tended to locate the "problem" of dietary restrictions within the dietaryrestricted. Contrary to the existing literature, we argue that such problems are sociocultural and institutional rather than pathological and individual. Our data illustrate that the quality of dietary‐restricted living improves when dietary‐restricted students advocate for and institutions respond to material, systemic solutions that allow the dietary‐restricted population to eat safely, socially, and quickly in a college environment, just like their non‐dietary‐restricted peers.